Customary Governance and State Legal System in Nepal - Thami, Tahal (Tri-Chandra Journal of Anthropology, 2024)
Indigenous governance systems are sui generis judicial, administrative, economic, and political systems for exercising authority and upholding the Indigenous governance system of Indigenous peoples. Those institutions help them to realize self-government, autonomy, and self-determination as enshrined in the United Nations Declaration on the Rights of Indigenous Peoples inter alia other legal instruments. In Nepal, the 2015 Constitution opened up avenues for the de jure acceptance of the Indigenous customary governance system at the local levels. De facto recognitions were in place for a long time at the local level despite national laws’ reticence and prejudice. This article looks into the convergent and divergent between customary governance and “nation-state” governing procedure and evaluates the long-term effects on self-rule, autonomy, and self-determination of Indigenous Peoples while interfacing with the contemporary state mechanisms. The indigenous worldview and inclusion/exclusion perspective is the theoretical/conceptual lenses for analyzing the phenomenon in this study. Talking circles, key informant interviews, focus group discussions observations, informal conversations, and participation in periodic assemblies of customary institutions were the strategies of data gathering. Despite the nonrecognition of federal laws, local governments in some parts of the country initiated recognizing customary governance. However, such initiatives, instead of allowing them to operate independently and guaranteeing self-determination, self-rule, and autonomy as the indigenous peoples’ movement demanded at the time, tended to subordinate and bring the customary governance system under the control and jurisdiction of the state law. That will be detrimental to the functioning of Indigenous political institutions in the long run.